2005
DOI: 10.1007/s00406-005-0593-7
|View full text |Cite
|
Sign up to set email alerts
|

Axis I disorders and personality disorders as risk factors for suicide

Abstract: There is a lack of psychological autopsy studies assessing the influence of axis I disorders on axis II disorders as risk factors for suicide. Therefore, we investigated the association between personality disorders, axis I disorders, and suicide. Psychiatric disorders were evaluated by a semi-structured interview including the Structured Clinical Interview for DSM-IV Axis I (SCID-I) and Personality Disorders (SCID-II) in 163 completed suicides (mean age 49.6 +/- 19.3 years; 64.4% men) and by personal intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 69 publications
7
47
3
3
Order By: Relevance
“…This is contrary to previous studies (Brent, Johnson, Perper et al, 1994;Foster, Gillespie, McClelland et al, 1999;Johnson, Cohen, Skodol et al, 1999;) reporting an association between CCPD and suicidal behavior. These studies did not exclude other PD co-morbidity, which could affect findings given that the cooccurrence of personality disorders from more than one cluster has been reported to be associated with elevated suicide risk (Schneider, Wetterling, Sargk et al, 2005). On the other hand, our findings differ from those of Schneider, Wetterling, Sargk et al (2005) who reported that, in a psychological autopsy study, presence of "pure" CCPD was a predictor of suicide only for men, even independently of axis I disorders.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This is contrary to previous studies (Brent, Johnson, Perper et al, 1994;Foster, Gillespie, McClelland et al, 1999;Johnson, Cohen, Skodol et al, 1999;) reporting an association between CCPD and suicidal behavior. These studies did not exclude other PD co-morbidity, which could affect findings given that the cooccurrence of personality disorders from more than one cluster has been reported to be associated with elevated suicide risk (Schneider, Wetterling, Sargk et al, 2005). On the other hand, our findings differ from those of Schneider, Wetterling, Sargk et al (2005) who reported that, in a psychological autopsy study, presence of "pure" CCPD was a predictor of suicide only for men, even independently of axis I disorders.…”
Section: Discussioncontrasting
confidence: 88%
“…These studies did not exclude other PD co-morbidity, which could affect findings given that the cooccurrence of personality disorders from more than one cluster has been reported to be associated with elevated suicide risk (Schneider, Wetterling, Sargk et al, 2005). On the other hand, our findings differ from those of Schneider, Wetterling, Sargk et al (2005) who reported that, in a psychological autopsy study, presence of "pure" CCPD was a predictor of suicide only for men, even independently of axis I disorders. In our study, there were no associations between gender and suicidal ideation or behavior in depressed patients with CCPD and those without co-occurrence of other personality disorders.…”
Section: Discussioncontrasting
confidence: 88%
“…The finding of a history of mental illness as an independent risk factor for suicide in our study is consistent with some studies in China [6,32,34] and Western countries [7,[54][55][56] . In Western cultures, psychological autopsy studies revealed that 90-95 percent of suicide victims had a diagnosable psychiatric disorder at the time of the suicide [1] , but only about half of suicide victims in China had a history of psychiatric diagnosis at the time of death [4,6,32,34] .…”
Section: Issn 2372-5923supporting
confidence: 93%
“…A psychiatric disorder, of which the commonest is an episode of major depression, is present in association with over 90 per cent of all suicides according to psychological studies conducted in the United States and western Europe [14][15][16][17][18]. Part of the neurobiology observed in recurrent major depression, that is present between episodes as well as during episodes, is a series of abnormalities in the serotonergic system [19].…”
Section: A Stress-diathesis Model Of Suicidal Behaviourmentioning
confidence: 99%